STANDAR KUALIFIKASI GURU DALAM KURIKULUM MERDEKA DI SMP NEGERI 27 MEDAN - Putri, Nur Annisa; Anissa , Siti; Zuhra, Siti Asyifa; Maulani , Yusriah (Yayasan Amanah Nur Aman, 2025)
The Independent Curriculum is an educational reform that emphasizes learning freedom and character strengthening of students. Teachers play a key role in the successful implementation of this curriculum. This study aims to examine the extent to which teacher qualification standards influence the implementation of the Independent Curriculum at SMP Negeri 27 Medan. The research method used is descriptive qualitative through interviews and observations involving teachers and students. The results show that teacher qualifications, which include pedagogical, professional, social, and personal competencies, significantly affect the success of the curriculum's implementation. Although some teachers welcome the Independent Curriculum and find its flexibility helpful, there are still implementation obstacles due to inadequate qualifications and understanding. Meanwhile, the majority of students struggle to adapt to the new learning model. This study emphasizes the importance of strengthening teacher qualifications to support the effectiveness of the Independent Curriculum.